Objective measurement of figure skating performance - Looney, M. A. (Journal of Outcome Measures, 1999)
Figure skating uses the median rank aggregation system for determining medal winners. Unfortunately, the system can be influenced by idiosyncratic ratings made by some judges unlike the skating ability measures from a many-facet Rasch analysis. These measures are constructed to be independent, as statistically possible, of item difficulties, judge severities, and the rating scale structure. A many-facet Rasch analysis was conducted on data from the controversial ladies event at the 1994 Olympics. The results illustrate how the idiosyncratic ratings of the judges were not accounted for by the median rank system, thus biasing the selection of the gold medal winner. All sports that rely on judges' ratings should investigate the use of a many-facet Rasch model in order to bring more objectivity and fairness to the winner selection process.